2013
DOI: 10.1007/s00114-013-1019-4
|View full text |Cite
|
Sign up to set email alerts
|

The ‘I see you’ prey–predator signal of Apis cerana is innate

Abstract: An 'I see you' (ISY) prey-predator signal can co-evolve when such a signal benefits both prey and predator. The prey benefits if, by producing the signal, the predator is likely to break off an attack. The predator benefits if it is informed by the signal that the prey is aware of its presence and can break off what is likely to be an unsuccessful and potentially costly hunt. Because the signal and response co-evolve in two species, the behaviour underlying an ISY signal is expected to have a strong genetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Such a preference is quite interesting as it underlines a rather evident specialisation in feeding behaviour of both species towards A. mellifera honeybee prey, although both species are considered semi-specialists (Matsuura, 1991). Honeybee colonies represent an excellent protein source for a growing nest of hornets (Ono et al, 1995); the high concentration of potential prey and the lack of effective defensive strategies (Tan et al, 2012(Tan et al, , 2013Arca et al, 2014) could explain the dietary preferences shown by workers in our trials. Thus, it is likely that, in case of beehive availability, hornets of both species would concentrate their foraging effort on the preferred prey, therefore increasing the chances of competition.…”
Section: Discussionmentioning
confidence: 70%
“…Such a preference is quite interesting as it underlines a rather evident specialisation in feeding behaviour of both species towards A. mellifera honeybee prey, although both species are considered semi-specialists (Matsuura, 1991). Honeybee colonies represent an excellent protein source for a growing nest of hornets (Ono et al, 1995); the high concentration of potential prey and the lack of effective defensive strategies (Tan et al, 2012(Tan et al, , 2013Arca et al, 2014) could explain the dietary preferences shown by workers in our trials. Thus, it is likely that, in case of beehive availability, hornets of both species would concentrate their foraging effort on the preferred prey, therefore increasing the chances of competition.…”
Section: Discussionmentioning
confidence: 70%
“…In its area of origin, V. velutina preys on Apis cerana and the introduced European honeybee, Apis mellifera . Contrary to A. cerana , A. mellifera is more vulnerable to vespid predators, presumably because it did not coevolve with this hornet species (Ken et al ., ; Tan et al ., , , , , ). In France, predation by V. velutina weakens native honeybee colonies toward the end of summer.…”
Section: Introductionmentioning
confidence: 99%
“…neckteeth in Daphnia sp. [6]), warning signals (including behaviours, sounds and colours, i.e., aposematism) or alternatively crypsis [7][11], and/or direct behavioural response (fleeing [12], feigning death [13], [14], attacking [15][18]). Conversely, predators are selected for their efficacy to acquire prey, i.e., in bypassing their defence [19][24].…”
Section: Introductionmentioning
confidence: 99%
“…In its native area, V. velutina hunts the native and the introduced honeybee species, Apis cerana and A. mellifera respectively. Apis cerana which is supposed to have co-evolved with V. velutina is able to exhibit efficient antipredator behaviours against this hornet species whereas A. mellifera is less defensive thus suffering a higher predation pressure [10], [11], [15][18]. The introduction of this hornet species into France generates the reversed situation, A. mellifera being the native prey and V. velutina the alien predator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation